Praxistransfer in der tertiären Bildungsforschung Modelle, Gelingensbedingungen und Nachhaltigkeit - Buchholtz, Nils; Barnat, Miriam; Bosse, Elke; Heemsoth, Tim; Vorhölter, Katrin; Wibowo, Jonas (Hamburg University Press, 2019)
For tertiary education research, the transfer of science into practice - and back - is a fundamental issue. What needs to be specified, however, is what kind of practice is involved, what conceptual understanding underlies transfer and under what conditions, objectives and success criteria transfer is considered. This volume brings together various contributions to describe the conditions for success, models and sustainability of transfer in the field of education. Researchers from higher education didactics, teacher training and further education and school development look at the topic together from their different perspectives. The contributions stem from an interdisciplinary conference for young researchers on the topic of practice transfer in tertiary educational research at the University of Hamburg in November 2017.